Civic Engagament Kampoeng Baca Pelangi Community in Educating and Reducing Psychological Impacts for Child Victims of the Lombok Earthquake - Ahmad Hudori; Dewi Gunawati; Triana Rejekiningsih (STKIP Melawi, 2021)
Abstract: This paper tries to discuss the Kampoeng Baca Pelangi community as an effort to educate and reduce the impact of the natural disaster in Lombok for child victims. Then the aim of his command was to explore the form of the Kampoeng Baca Pelangi community in educating and reducing the psychological impact for children who were victims of the Lombok earthquake. Indonesia is a country prone to natural disasters. Based on data compiled from the National Disaster Management Agency (BNPB), it is stated that during 2020, starting from January 1, 2020 to December 28, 2020, there were 2,925 natural disasters throughout Indonesia. This paper uses a qualitative approach with a case study method. The findings in this study are in terms of educating children about the impact of natural disasters, the Kampoeng Baca Pelangi community takes steps such as: (1) Identifying children affected by disasters and planning appropriate activities for them, (2) providing time for children to discuss disasters, (3) careful group discussions for children, (4) encourage children not to consume news too much, (5) encourage children to continue if possible. Meanwhile, to reduce the impact of natural disasters, the Kampoeng Baca Pelangi community applies traumatic counseling strategies. Traumatic counseling is divided into three stages, (1) the initial stage of counseling, (2) the middle stage of counseling, (3) the final stage of counseling. Keywords: Kampoeng Baca Pelangi community, psychological impacts, child victims, Lombok Earthquake